Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Some people say, Johann Bernoulli has proven $\ln z=\ln (-z)$ in the following way $$\ln ((-z)^2 )=\ln(z^2)\;\;\;\Rightarrow\;\;\;2\ln(-z)=2\ln z\;\;\;\Rightarrow\;\;\;\ln (-z)=\ln z$$ While the statement is not true, I'm unable to figure out what exactly went wrong:

  • Since $(-z)^2=z^2$ for all $z\in\mathbb{C}$, it holds $\ln ((-z)^2 )=\ln(z^2)$, too.
  • By definition of $a^b=e^{b\ln a}$ for all $a\in\mathbb{C}^{-},b\in\mathbb{C}$ it follows $\ln (e^{2\ln z})=\ln (e^{2\ln (-z)})$ for all $z\in\mathbb{C}\setminus\mathbb{R}$
  • Further, for $z=re^{i\varphi}$ we've got $$\ln (e^{2\ln z})=\ln (r^2)+i\pi +i\text{arg}_0(e^{i(2\varphi -\pi)})=2\ln r+2i\varphi$$ and $$\ln z=\ln r+i\varphi$$ So, it seems like $2 \ln z=\ln (z^2)$ holds, too (at least for all $z\in\mathbb{C}\setminus\mathbb{R}$).

So, what is wrong here?

PS: Let's define $$\mathbb{C}^{-}:=\left\{z\in\mathbb{C} : \text{Re }z>0\vee \text{Im}\ne 0\right\}$$

share|cite|improve this question
For the real logarithm, we actually have that $\;\log z^2=2\log|z|\;$ . For the complex logarithm things are way messier as some exponents rules we're used to in real analysis don't even apply here... – DonAntonio May 17 '14 at 15:23
Possible duplicate of… – Barry Cipra May 17 '14 at 15:23
Not a duplicate at all. – Git Gud May 17 '14 at 15:24
Related: – Did May 17 '14 at 15:44
up vote 7 down vote accepted

Let's see where things go wrong. I'm going to assume my logarithm has a branch cut along the negative $x$-axis as per usual (and that we're looking at the principal argument where $\theta$ is between $-\pi$ and $\pi$ for symmetry). If $z = re^{i\theta}$

$$\log(z) \stackrel{\text{def}}{=} \log r+i\theta.$$

With a branch cut, $-z$ is a little ambiguous. If $\theta < 0$, then $-z = re^{i\theta+i\pi}$. If $\theta > 0$, then $-z = re^{i\theta-i\pi}$. Let's consider each case separately.

Case 1: $\theta < 0$, then

$$\log(-z) = \log(re^{i\theta+i\pi}) = \log r + i(\theta+\pi).$$

Note that this is most definitely not the same as $\log(z)$.

Case 2: $\theta > 0$, then

$$\log(-z) = \log(re^{i\theta-i\pi}) = \log r + i(\theta-\pi).$$

Similarly, this is not the same as $\log(z)$.

The question then becomes: where's the faulty assumption in his proof?

Clearly $(-z)^2 = z^2$ is true but complex logarithms no longer obey $\log(ab) = \log(a)+\log(b)$ in the usual way. If $a = r_1e^{i\theta_1}$ and $b = r_2e^{i\theta_2}$ (let's say neither of them are pure imaginary), then $\log(ab) = \log(r_1r_2 e^{i\theta_1+i\theta_2})$. What this evaluates is heavily predicated on what $\theta_1$ and $\theta_2$ are.

Suppose $-\pi < \theta_1+\theta_2 < \pi$, then indeed $\log(ab) = \log(r_1r_2)+i(\theta_1+\theta_2)$ which agrees exactly with $\log(a)+\log(b)$.

However suppose that $\theta_1+\theta_2>\pi$, then similar to above above, we would have that $\log(ab) = \log(r_1r_2)+i(\theta_1+\theta_2-2\pi) \neq \log(a)+\log(b)$.

If instead $\theta_1+\theta_2 < -\pi$, then $\log(ab) = \log(r_1r_2)+i(\theta_1+\theta_2+2\pi) \neq \log(a)+\log(b)$.

If you restrict to the case that $a = b = -z$, the above analysis would read that $\log((-z)^2) = 2\log(-z)$ if (and only if) $\theta < \left|\frac{\pi}{2}\right|$ as Did mentions below. So really the discrepancy is due to the periodic nature of $e^{i\theta}$ (and hence the multivalued nature of $\log$).

share|cite|improve this answer
What was your intent by declaring $k\in\mathbb{Z}$? – 0xbadf00d May 17 '14 at 19:38
I was going to treat the logarithm as being a multivalued function at first but decided to change my mind. I just forgot to change everything (and left that little bit by accident). – Cameron Williams May 17 '14 at 19:40
Is there any reason why we assume $a,b$ to be not pure imaginary? – 0xbadf00d May 17 '14 at 19:43
Because then their product would be negative and the logarithm wouldn't be defined. – Cameron Williams May 18 '14 at 20:40

Of course the identity $\mathrm{Log}(z^2)=2\ln(r)+2\mathrm i\varphi$ when $z=r\mathrm e^{\mathrm i\varphi}$, holds only when $-\frac\pi2\lt\varphi\leqslant\frac\pi2$ although the identity $\mathrm{Log}(z)=\ln(r)+\mathrm i\varphi$ holds for every $-\pi\lt\varphi\leqslant\pi$ (recall that by definition the principal value $\mathrm{Log}(z)$ is the logarithm whose imaginary part lies in the interval $(−π,π]$).

For a little practice, choose $z=-1+\mathrm i\sqrt3$, compute $r$, $\varphi$, $\ln(r)$, $\mathrm{Log}(z)$ and $\mathrm{Log}(z^2)$, and compare.

share|cite|improve this answer

the key point is that $z^2=y^2 \implies z=y$ is false for $z,y \in \mathbb C$ just like it is for $z,y \in \mathbb R$

which then falls into the classic take square root of both sides without adjusting signs where needed

share|cite|improve this answer

Let's start from your first display: $$ \log((-z)^2 )=\log(z^2) \implies 2\log(-z)=2\log z\implies \log (-z)=\log z $$ (I find anachronistic using “ln”, which I find awful anyway).

The “error” is in the first implication, which requires, assuming $z>0$, that

  1. the logarithm exists for negative numbers;

  2. it satisfies the same property for exponents as the logarithm for positive numbers.

Actually, there is no error: Bernoulli's argument is no more than a motivation for a definition. After having defined the logarithm for positive numbers, Bernoulli wants to extend it by setting $\log z=\log(-z)$ for $z<0$ or, in other words, $$ \log z=\log|z|\qquad(z\ne0). $$

Do the common properties hold? Yes, because $|xy|=|x|\,|y|$, so also $|z^n|=|z|^n$ (at least when $n$ is an integer).

This is, in a way, no different from extending the Gamma function to negative numbers by using the property that $\Gamma(t+1)=t\Gamma(t)$ for $t>0$, which can be proved from the definition $$ \Gamma(t)=\int_0^{\infty}x^{t-1}e^{-x}\,dx $$ (for $t>0$). Thus we can define, for $-1<t<0$, $$ \Gamma(t)=\frac{\Gamma(t+1)}{t} $$ and go backwards, using this definition for getting $\Gamma(t)$ when $-2<t<-1$, and so on.

What's the difference between these two cases? That the $\Gamma$ function can be shown to be extendable to the whole complex plane (except at the nonpositive integers): $$ \Gamma(t)= \frac{e^{-\gamma t}}{t}\prod_{n\ge1}\left(1+\frac{t}{n}\right)^{-1}e^{t/n} $$ (where $\gamma$ is the Euler-Mascheroni number).

Bernoulli's extension of the logarithm to the negative numbers, instead, has no relationship with the exponential function any more. It's just one possible extension, but it turns out to be useless. The reasons for its uselessness have been given in other answers.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.